Building community in student unions - Solheid, Lacey (Kansas State University, 2014)
For just over 100 years, student unions have served college campuses across the United States. These buildings have changed and progressed over time to offer services to fit the needs of students. Recently, the concept of community building has become increasingly more important to higher educational institutions. Student unions are at the very center of community building on college campuses. This report looks at one model of community building and offers design elements union administrators need to be aware of when designing student union spaces.
Keywords: Community; Student unions; Higher Education (0745)